Fundamentals of writing for marketing and public relations a step-by-step guide for quick and effective results - Mizrahi, Janet (Corporate communication collection, 2010)
List of illustrations -- Acknowledgments -- 1. Basic writing guidelines -- 2. Writing news releases -- 3. Writing newsletters -- 4. Writing brochures -- 5. Writing web copy -- 6. Writing for social media: blogs and microblogs -- 7. Media kits -- Notes -- References -- Index